2020
DOI: 10.1038/s41598-020-69236-z
|View full text |Cite
|
Sign up to set email alerts
|

SIRT7 deficiency suppresses inflammation, induces EndoMT, and increases vascular permeability in primary pulmonary endothelial cells

Abstract: Acute lung injury (ALI), a common condition in critically ill patients, has limited treatments and high mortality. Aging is a risk factor for ALI. Sirtuins (SIRTs), central regulators of the aging process, decrease during normal aging and in aging-related diseases. We recently showed decreased SIRT7 expression in lung tissues and fibroblasts from patients with pulmonary fibrosis compared to controls. To gain insight into aging-related mechanisms in ALI, we investigated the effects of SIRT7 depletion on lipopol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 63 publications
0
17
0
Order By: Relevance
“…Supporting our results, Miyasato, Y. et al, reported that Sirt7 deficient mice, suffering from cisplatin nephrotoxicity, exhibited a reduction in Tnfa, Il1b, Il6, Ccl2 , and Cxcl2 mRNA levels, as well as in F4/F80 positive cells compared to WT mice [ 38 ]. Moreover, it has been reported that Sirt7 deficiency protects against pulmonary endothelium inflammation induced by lipopolysaccharides, an effect that was associated with an increase in TGFβ1 expression and its target genes, driving endothelium-mesenchyme transition to promote cellular repair [ 39 ]. Interestingly, we also found that after IR, the KO-Sirt7 mice had a significant increase in Tgfb1 mRNA levels that was not seen in the WT+IR and HT-Sirt7 groups.…”
Section: Discussionmentioning
confidence: 99%
“…Supporting our results, Miyasato, Y. et al, reported that Sirt7 deficient mice, suffering from cisplatin nephrotoxicity, exhibited a reduction in Tnfa, Il1b, Il6, Ccl2 , and Cxcl2 mRNA levels, as well as in F4/F80 positive cells compared to WT mice [ 38 ]. Moreover, it has been reported that Sirt7 deficiency protects against pulmonary endothelium inflammation induced by lipopolysaccharides, an effect that was associated with an increase in TGFβ1 expression and its target genes, driving endothelium-mesenchyme transition to promote cellular repair [ 39 ]. Interestingly, we also found that after IR, the KO-Sirt7 mice had a significant increase in Tgfb1 mRNA levels that was not seen in the WT+IR and HT-Sirt7 groups.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the immune system, SIRT7 silencing reduced lipopolysaccharide (LPS)-induced pro-inflammatory effects and induced an endomesenchymal transition that increased endothelial barrier permeability. All this is a consequence of the suppression of NFκB signaling and the resulting low levels of ICAM1, VCAM1, IL8, IL6, cadherin, and PECAM1, but increases in collagen, αSMA, TGFβR1, and SNAIL [ 105 ]. SIRT7 interacts with RAN and deacetylates it at residue K37, leading to decreased binding between RAN and nuclear export components and, as a consequence, retention of NF-κB p65 in the nucleus [ 106 ].…”
Section: Sirt7 Association With Agingmentioning
confidence: 99%
“…Claudin-18 deficiency results in alveolar barrier dysfunction and impaired alveologenesis [13,15]. Impaired TJ structure and/or function have also been reported in mice deficient in lymphoblastic leukemia-derived sequence (Lyl)-1, Crumbs (Crb3), and sirtuins (SIRTs) [28][29][30].…”
Section: Genetic Mouse Models Of Tj Proteinsmentioning
confidence: 99%